Altered unfolded protein response and proteasome impairment in pseudoexfoliation pathogenesis. (April 2019) - Hayat, Bushra; Padhy, Biswajit; Mohanty, Pranjya Paramita; Alone, Debasmita Pankaj
Abstract: Pseudoexfoliation (PEX), an ocular disorder involving deposition of proteinaceous fibrils on the surface of anterior eye tissues, is a major contributing factor to worldwide glaucoma. Excessive production and accumulation of fibrillar materials in PEX could be an indication of proteostasis imbalance. This study aims at investigating the differential expression of various genes involved in unfolded protein response and ubiquitin proteasome pathway in pseudoexfoliation (PEX) patients compared to non-PEX controls using lens capsule tissue as the study material. The custom RT 2 Profiler PCR array was used to identify a set of stress-related candidate genes that were differentially expressed in PEX. The expression of the highly deregulated genes was validated by qRT-PCR and subsequently their protein expression was checked through immunoblotting and immunostaining. Proteasome-Glo based assay and TUNEL assay were employed to detect specific proteasomal activity and apoptotic activity, respectively in the study subjects. Increased ER stress markers, Synoviolin1, Eukaryotic initiation factor 2-alpha kinase 3, DnaJ (Hsp40) homolog, subfamily B, member 11, Caspase 12, Heat shock 70 kDa protein 5, Heat shock 60 kDa protein 1 and Calnexin were observed in the lens capsule of PEX individuals compared to age-matched controls. On the other hand, increased ubiquitin B mRNA expression followed by significant downregulation of proteasome subunits; 26 S proteasome non-ATPase regulatory subunit 1, and proteasome subunit alpha-type 5 was found in pseudoexfoliation syndrome (PEXS) individuals. Decrease in chymotrypsin-like proteasome activity and increased apoptosis were also observed in PEX subjects. The present findings provide evidence for alterations in endoplasmic reticulum–related stress response and ubiquitin proteasome function in lens capsule of PEX individuals. Altogether, our study has identified deregulated expression of candidate genes in ER-UPR pathway and implicates proteasome impairment as a causative factor in PEX pathogenesis. Highlights: Increased expression of ER-stress markers, Synoviolin1 and Calnexin suggests UPR activation in PEX. Reduced proteasome activity and proteasome subunit expression indicate impaired proteasome function. Increased apoptosis was seen in the lens capsules of PEXS and PEXG individuals.